Geomagnetic field at Slovak repeat stations – the 2004.5 epoch - VALACH, Fridrich; VÁCZYOVÁ, Magdaléna; DOLINSKÝ, Peter (Contributions to Geophysics and Geodesy, 2021)
The paper is devoted to the results of the last geomagnetic repeat station survey in Slovakia that was carried out in 2004. The geomagnetic elements at the observation points of the repeat station network were reduced to the 2004.5 epoch. The rates of their secular changes were derived for the period between 1995.5 and 2004.5. Linear models for the distribution of the geomagnetic elements and their secular variations on the Slovak territory are presented in the paper, too.